-3+p/6=-5

Simple and best practice solution for -3+p/6=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3+p/6=-5 equation:


-3+p/6=-5

We simplify the equation to the form, which is simple to understand
-3+p/6=-5

We move all terms containing p to the left and all other terms to the right.
+ 0.16666666666667p=-5+3

We simplify left and right side of the equation.
+ 0.16666666666667p=-2

We divide both sides of the equation by 0.16666666666667 to get p.
p=-12

See similar equations:

| -6.9x+23.3831=-1.1(x-4.237) | | (-2+-2y)+3y=-4 | | 4+11x=7x-1 | | 7x+23x-5=6(5x+8) | | 10x-9=-11 | | 936-(x+24)=72 | | 4x-4+2y=0 | | (9-r)3-12r=33 | | 2(4s+5)-4s=2(2s+4)-9 | | 100y+20x+100= | | 3(x-5)=5(x+5) | | C=0.5x+8x+4000 | | -j+-13j= | | 7-7n+5n=16-55 | | x+(-19)=31 | | (7x+5)+(4x+2)= | | 4(2y-2)=24 | | -5(n-1)-6n=-6(n+4)-1 | | 2r-(5-r)=13*2r | | 1+2+2x=31 | | f(x)=3x^2-7x-30 | | x^4-4x^3+3X=0 | | x(-19)=31 | | (R-9)3-12r=33 | | 8=-m | | 18x^4+25x^2=3 | | 2x-10=2(x-5)-5 | | 9y+3y=216 | | x-(19)=31 | | y=(x-a)m | | 3n-7=8n+11 | | .06(10000)+0.08x=0.072(10000+x) |

Equations solver categories